Central nervous system–immune reconstitution inflammatory syndrome presenting as varicella zoster virus-mediated vasculitis causing stroke. (August 2014) - Teo, SY; Raha, D; Warren, D; Hassan, A; Monteiro, E
Varicella zoster virus (VZV)-mediated vasculitis is a rare cause of stroke, but should be considered in HIV patients where vasculitis can occur in association with central nervous system – immune reconstitution inflammatory syndrome (CNS-IRIS). A literature search revealed 7 reports of VZV vasculitis over the years with no unifying management strategy, highlighting the difficulty in managing rare conditions in the absence of clear guidelines. This is the first documented case of VZV-mediated vasculitis presenting as stroke in the United Kingdom. Our patient made a full recovery with multidisciplinary input from HIV, neurology and radiology specialists.